Vibratory feedback for artificial hands - Mohamad Hanif, Noor Hazrin Hany; Chappell, Paul H.; Cranny, Andy; White, Neil M. (IEEE, 2013)
One of the capability of a prosthetic hand device that is highly preferred is that it should be able to mimic the functionality of the lost arm, and that loss includes the tactile sensory system. A miniature DC motor has been identified to be the best haptic actuator to deliver the required sensory feedback. Experiments and simulations were carried out to predict the transient responses, driving frequencies as well as vibration amplitude of the motor. The results have shown that the motor is reliable in matching the optimum frequency response of the mechanoreceptors in the residual arm, which is important in providing an efficient supplementary sensation.